Nutritional profile of newborns with microcephaly and factors associated with worse outcomes - dos Santos, Samira Fernandes Morais (Clinics (Sao Paulo), 2019)
OBJECTIVE: To describe the nutritional profile of newborns with microcephaly and factors associated with worse outcomes during the first 14 days of life. METHODS: This investigation is a longitudinal, descriptive study carried out in 21 full-term neonates exposed vertically to the Zika virus and hospitalized in a neonatal intensive care unit from February to September 2016. Patients receiving parenteral nutrition were excluded. Data analysis was performed using a generalized estimating equation model and Student’s t-test to evaluate the association between worsening weight-for-age z-scores and independent clinical, sociodemographic and nutritional variables during hospitalization, with p<0.05 indicating significance. RESULTS: During hospitalization, there was a decrease in the mean values of the weight-for-age z-scores. The factors associated with worse nutritional outcomes were symptomatic exposure to the Zika virus, low maternal schooling, absence of maternal income and consumption of infant formula (p<0.05). Calcification and severe microcephaly were also associated with poor nutritional outcomes. Energy and macronutrient consumption remained below the recommendations and had an upward trend during hospitalization. CONCLUSION: The presence of cerebral calcification, the severity of microcephaly and symptomatic maternal exposure to Zika virus affected the nutritional status of newborns. In terms of nutritional factors, human milk intake had a positive impact, reducing weight loss in the first days of life. Other known factors, such as income and maternal schooling, were still associated with a poor nutritional status.